Peran Generasi Milenial Dalam Religious Moderation - Moh. Muntholib; Nelud Darojatul Aliyah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Indonesian culture, ethnicity, race, language and religion are very diverse. Millennial young men and women must be present to mediate disputes with knowledge and religious moderation. The aim of this research is to determine the role of the millennial generation in religious moderation. This research uses library research methods, which means collecting data or searching for journals in libraries and other sources that provide books and other informational materials. One example of a library research source is Google Scholar, which can be used to search for journals. Additionally, they use a naturalistic approach, which is a type of qualitative research that aims to provide a deeper understanding of the breadth of a phenomenon in a specific context. The millennial generation plays a very important role in building religious moderation in Indonesia. They can function as figures or agents of change who spread the message of religious moderation into society, such as holding outreach, utilizing technology, and being involved in positive activities, such as organizing. Millennial youth can help create a more harmonious, peaceful and tolerant environment by understanding and implementing religious moderation.